FRI0286 Diffuse alveolar hemorrhage in patients with systemic lupus erythematosus. a subgroup analysis. (23rd January 2014) - Martinez-Martinez, M. U.; Alcocer-Varela, J.; Merayo-Chalico, F. J.; Gómez-Bañuelos, J. D.J.E.; Saavedra, M. A.; Enciso-Peláez, S.; Faugier-Fuentes, E.; Maldonado-Velázquez, R.; Suárez-Larios, L. M.; Vega-Morales, D.; Abril, A.; Butendieck, R.; et al.
Abstract : Background: Diffuse alveolar hemorrhage (DAH) is a rare life-threatening complication in systemic lupus erythematosus (SLE). It is associated with a high mortality rate. Pathogenesis of DAH in patients with SLE includes disease activity; however, infection was demonstrated in more than 50% in other case series. Objectives: To evaluate subgroups in a large retrospective cohort of SLE patients with DAH. Methods: This retrospective cohort included 57 patients with SLE and DAH from 8 hospitals. We evaluated clinical, laboratory and treatment data. All patients met the American College of Rheumatology classification criteria for SLE. DAH was defined according to the presence of sudden drop of hemoglobin of at least 1.5 g/dL without other sources of bleeding, new infiltrates on chest radiograph and at least one of the following pulmonary symptoms: hemoptysis, dyspnea, or tachycardia. Non-parametric statistics were performed; categorical variables were compared with X 2 or exact Fisher-test. Results: We included 57 patients with DAH and SLE, 49 (86%) were women, 14 (24.6%) children, and 24 (42.1%) died. Twenty two patients (38.6%) were diagnosed with infection (8 invasive fungal infections, 21 bacterial infections, 7 patients had mixed infections). Factors associated with mortality were: high disease activity (relative risk (RR)=2.1, confidence interval (CI): 1.1-4.1, p=0.0239), glomerular filtration rate less than 60 ml/min/1.72 m 2 (RR: 2.5, CI: 1.2-5.1, p=0.0052), mechanical ventilation (RR: 7.5, CI: 1.1-50.5, p-value= 0.002), infections (1.9, CI: 1.03- 3.5, p=0.04) and specifically fungal infections (RR: 2.0, CI: 1.2-3.5, p= 0.04). There were no differences in mortality rates between children and adults. Table 1 shows factors associated with infection, and that SLE treatment naïve as a "protective" factor. Conclusions: DAH in SLE patients is frequently associated with infection; our series describes a subgroup analysis of this rare manifestation of SLE. Factors associated with infection can indicate therapeutic choice for the rheumatologists in SLE patients with DAH. Disclosure of Interest : None Declared